Medicinal plants of the Mien (Yao) in Northern Thailand and their potential value in the primary healthcare of postpartum women - Panyaphu,K. (Elsevier Ireland Ltd, 2015)
Aim of the study: To study the use of medicinal plants by the Mien in Nan Province and their potential value in the primary healthcare of postpartum women. Also, to survey the medicinal plant resources present there. Materials and methods: Free listing and interviews were used with four key informants (herbalists and collectors) to collect all qualitative and quantitative plant data. Semi-structured questionnaires were used to obtain information on the knowledge, attitude and practices of fifty-eight non-specialist informants. Transect walks of forest plots were carried out with herbalists to get more information on the status of the medicinal plants with regard to their habitat. Results and conclusion: More than 168 species of medicinal plants were surveyed. These plants belonged to 80 families and 145 genera, of which 131 were wild plants and 37 species have been cultivated in home gardens. The interview data from four herbalists and fifty-eight non-specialist informants indicated that the majority of non-specialist informants who used medicinal plants were women and the most common usage categories were for birth related conditions (44 species, 26.2%). The most common method of preparation was decoction for both oral consumption and bathing uses (134 species, 79.8%). The most common species of medicinal plants were used in a postpartum herbal bath formulae and in food supplement formulas. These were Anredera cordifolia (Ten.) Steenis, Basella alba L., Ricinus communis L., Poikilospermum suaveolens (L.) Merr., Gouania leptostachya DC. Var. leptostachya, Schefflera sp. cf. Schefflera bengalensis Gamb., Blumea balsamifera (L.) DC., Chromolaena odoratum (L.) King et Robin and Cymbopogon citratus (DC.) Stapf. © 2011 Elsevier Ireland Ltd. All rights reserved.